Antioxidant Activity and Quality of Frozen Yoghurt with Moringa oleifera Lamk. Leaves Extract - Sari, Primaningrum Dian Indah; Swasti, Yuliana Reni; Purwijantiningsih, Ekawati (agriTECH, 2025)
Moringa oleifera Lamk. (Moringa) is a plant widely distributed across various regions in Indonesia. The leaves of Moringa oleifera Lamk. contain higher nutritional value in protein and minerals compared to the green vegetables that are commonly consumed. This plant can be used to improve the quality of frozen yoghurt, a functional food that is currently popular due to the existence of Lactic Acid Bacteria (LAB), which is good for digestion. Therefore, this research aimed to improve the nutritional quality of frozen yoghurt using Moringa oleifera Lamk. Leaves Extract (MOLE), which is high in antioxidants and protein. However, MOLE does not reduce the viability of LAB. The viability of LAB decreases when phytochemical content with the ability as an antibacterial is added. The soluble fiber content of MOLE is able to improve the texture of frozen yoghurt. In this research, four different frozen yoghurt samples were produced with the addition of MOLE in various ratios (0%, 10%, 20%, and 30%). The analysis shows that frozen yoghurt with 30% MOLE produces the highest antioxidant activity and viability of probiotics. The content of product with 30% MOLE includes 2.85±0.13% fat, 10.07±0.44% protein, 1.10±0.01% ash, 26.4±0.35% total solid (TS), 21.67±0.58% total soluble solid (TSS), 78.66±1.31% overrun, 807±5.77 (s) melting rate, 0.86±0.02% titratable acidity, and 5.4±0.02 pH. It also contains 8.58±0.52 log CFU/mL LAB, Salmonella negative/25 g, 102.26±0.13 mg GAE/100 mL of total phenolic, and 87.78±0.64% of antioxidant activity.